Diagnostic role of 11C-Pittsburgh compound B retention patterns and glucose metabolism by fluorine-18-fluorodeoxyglucose PET/CT in amnestic and nonamnestic mild cognitive impairment patients. Issue 11 (November 2016) - Jiménez-Bonilla, Julio F.; Banzo, Ignacio; De Arcocha-Torres, María; Quirce, Remedios; Martínez-Rodríguez, Isabel; Lavado-Pérez, Carmen; Bravo-Ferrer, Zully; Rodríguez-Rodríguez, Eloy; Sánchez-Juan, Pascual; Carril, José M.
Abstract : Objective: Amyloid imaging clinically is usually reported as positive or negative, and the role of amyloid topography has not been studied before. To evaluate in a clinical setting the regional distribution patterns of 11 C-Pittsburgh compound B ( 11 C-PIB) and the fluorine-18-fluorodeoxyglucose ( 18 F-FDG) uptake in patients with mild cognitive impairment (MCI), we designed this study. Methods: We studied 81 consecutive MCI patients, 64 amnestic (A-MCI) and 17 nonamnestic (NA-MCI) by 11 C-PIB and 18 F-FDG PET/computed tomography, by visual analysis. PIB retention was classified according to the regional distribution into the following patterns: A (frontal, lateral temporal, basal ganglia and anterior cingulate) and B (global retention). 18 F-FDG images were considered positive only if temporoparietal hypometabolism consistent with Alzheimer's disease was observed. Results: In 42 of the 64 A-MCI, 11 C-PIB was positive. Twelve of the 42 positive A-MCI showed an A-pattern, all 18 F-FDG negative, and 30 a B-pattern, 10 18 F-FDG positive and 20 18 F-FDG negative. Of the 17 NA-MCI, 11 C-PIB was positive in three and 18 F-FDG was positive in one. The different proportion of 11 C-PIB positivity in A-MCI and NA-MCI was highly significant ( P <0.001). Conclusion: Two different 11 C-PIB patterns were observed in MCI patients and for the A-pattern, glucose hypometabolism consistent with Alzheimer's disease is highly unlikely. These findings may contribute towards a better selection of patients for future potential treatments and also to optimize the use of 18 F-FDG-PET/CT.